Pengaruh Kecepatan Putar Poros terhadap Massa dan Volume Bakso yang Dihasilkan pada Vertical Meatballs Machine - Cahyo Budi Nugroho; Nidia Yuniarsih; Soni Widiawan (JURNAL INTEGRASI, 2015)
Shape and size is influence by molding and batter separate. This research is to find the influence of velocity to results statistically. Research of the velocity influence is to know about is the mass and volume that produced in meatballs molding machine with Vertical Meatballs Machine can be different. The testing velocity at 50, 60, 80, 90, dan 100 rpm. To calculate velocity (rpm) that ideal, the data is calculate using deviation standard equation (deviation value) from data of mass and volume. Ini mass testing of meatballs, the highest value is velocity at 50 rpm that is 36,4 grams, whereas the lowest value is velocity at 100 rpm that is 19,4 grams. Ini volume testing of meatballs, the highest value is velocity at 50 rpm that is 39 ml, whereas the lowest value is velocity at 100 rpm that is 20 grams. According to the deviation standard equation in testing mass, the velocity in 60 rpm is the most ideal velocity because it is 0,84 as the lowest deviation .